2015
DOI: 10.1164/rccm.201406-1165oc
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Detection of Recent Tuberculosis Infection in Children in a High Tuberculosis–HIV Burden Setting

Abstract: Rationale: Children who are young, malnourished, and infected with HIV have significant risk of tuberculosis (TB) morbidity and mortality following TB infection. Treatment of TB infection is hindered by poor detection and limited pediatric data.Objectives: Identify improved testing to detect pediatric TB infection.Methods: This was a prospective community-based study assessing use of the tuberculin skin test and IFN-g release assays among children (n = 1,343; 6 mo to ,15 yr) in TB-HIV high-burden settings; ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 40 publications
2
41
0
1
Order By: Relevance
“…Although previous studies have shown that TB diseased individuals with advanced HIV disease may be less infectious [25, 26], we demonstrated a 1.43 fold increased chance of detecting an additional TB case in households known to be HIV-affected. Consistent with findings of smaller household contact tracing studies conducted within a research platform [19], we demonstrate that in our large interventional program contacts continued to be more likely to have TB disease if they were younger than 5 years of age (OR = 2.01), reported HIV-infection (OR = 4.9), reported one or more TB symptoms (OR = 7.70), or shared a bed with the index case (OR = 1.65). In contrast, contacts with unknown HIV status were less likely to have TB disease (OR = 0.63).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although previous studies have shown that TB diseased individuals with advanced HIV disease may be less infectious [25, 26], we demonstrated a 1.43 fold increased chance of detecting an additional TB case in households known to be HIV-affected. Consistent with findings of smaller household contact tracing studies conducted within a research platform [19], we demonstrate that in our large interventional program contacts continued to be more likely to have TB disease if they were younger than 5 years of age (OR = 2.01), reported HIV-infection (OR = 4.9), reported one or more TB symptoms (OR = 7.70), or shared a bed with the index case (OR = 1.65). In contrast, contacts with unknown HIV status were less likely to have TB disease (OR = 0.63).…”
Section: Discussionsupporting
confidence: 86%
“…This was similar to yield reported from other contact tracing programs conducted in TB high-burden settings that included adult and child index cases with all forms of TB; three studies from the Democratic Republic of Congo (2.2%, 2.8%, and 1.3% yield) and one from Pakistan (0.6% yield) [9]. In comparison, research studies have identified TB in 8 to 10% of child contacts in TB high-burden settings, highlighting the potential yield of child TB contact tracing given robust resources[19, 20]. The NNS to find an additional bacteriologically confirmed TB case consistently decreased as the age of the index case and the age of the contacts increased.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, evidence from the available studies are contrasting and some reports suggest that IGRAs are not more sensitive than TST in identifying M. tuberculosis infection in children, particularly <5 years of age and in high TB burden settings (TABLE 1) [9][10][11][12][13][14][15]. However, a recent study in TB-HIV high-burden settings on 1343 children between 6 months and 15 years of age showed that IGRA correlated better than the TST (p = 0.0011) and indeterminate IGRA results were not associated with age [16]. Combining IGRA with TST may improve the sensitivity and the use of both tests can increase the rate of positive results in high-risk settings [3,6,14,[17][18][19].…”
Section: Ifn-g Release Assaysmentioning
confidence: 99%
“…A study done in South African children by Mandalakas and colleagues also suggests that the T-SPOT.TB may offer advantages over the QGIT in the pediatric population, where diagnosis of latent and active TB is notoriously difficult (9). This prospective, observational cohort study assessed the likelihood of the tuberculin skin test (TST), the QGIT, and the T-SPOT.TB to predict latent disease in more than 1,300 children aged 6 months to 15 years.…”
Section: Diagnosis Of Latent and Active Diseasementioning
confidence: 99%